Longterm Monitoring of Nitrification and Nitrifying Communities during Biofilter Activation of Two Marine Recirculation Aquaculture Systems (RAS) - Sabine Keuter; Stefanie Beth; Gerrit Quantz; Carsten Schulz; Eva Spieck (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
Biofilters are crucial and costly components in marine recirculating aquaculture systems. However, not much is known about the settlement of nitrifying organisms and developing nitrification rates during the start-up phases of these reactors. The nitrifying microorganisms in moving bed biofilters of two marine recirculation aquaculture systems identical in construction were monitored for 388 and 477 days by PCR based methods, accompanied by laboratory nitrifying activity tests. Ammonia and nitrite were added to the recirculating aquaculture system 1, while system 2 was spiked with fish feed. On day 88, system 1 was stocked with turbot (at 17 °C) and on day 126 system 2 was stocked with sea bass cultivated at 22 °C. The potential nitrification rates corresponded well to the conditions in the operating systems, and in both systems slowly developing nitrite oxidation rates led to high nitrite peaks. However, after 218 (biofilter 1) and 286 (biofilter 2) days, potential rates of nitrite oxidizing bacteria outreached those of ammonia oxidizing bacteria.       The nitrite oxidizing bacteria were remarkably diverse on the genus level, and for the first time Nitrotoga was detected in marine biofilter systems. Nitrospira was assumed to be the most dominant nitrite oxidizing bacterium, also confirmed by electron microscopy. The ammonia oxidizing organisms belong almost exclusively to Nitrosomonas, of which dominant species shifted in both systems over time. The high similarities of some 16S rRNA gene sequences of Nitrospira and Nitrosomonas to sequences found previously in other marine recirculating aquaculture systems suggested that the species are characteristic for this artificial ecosystem.